2004
DOI: 10.1097/00002030-200404300-00010
|View full text |Cite
|
Sign up to set email alerts
|

Colour-Doppler ultrasonography of carotid vessels in patients treated with antiretroviral therapy

Abstract: These data confirm the higher prevalence of premature carotid lesions in the PI-treated patients. A periodic ultrasonographic study of the vascular wall should be included in the follow-up of HIV infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
6
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 17 publications
5
63
6
4
Order By: Relevance
“…Previous observational studies that investigated the relationship between protease inhibitor and carotid plaques produced conflicting results [19,23,[29][30][31]. Maggi demonstrated that protease inhibitor exposure was associated with carotid plaques [29,30] while other observational studies failed to show this association [19,23,31]. Although protease inhibitor exposure was not significantly associated with abnormal carotid ultrasound in our analysis, we found that longer duration of antiretroviral therapy was associated with an abnormal result.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Previous observational studies that investigated the relationship between protease inhibitor and carotid plaques produced conflicting results [19,23,[29][30][31]. Maggi demonstrated that protease inhibitor exposure was associated with carotid plaques [29,30] while other observational studies failed to show this association [19,23,31]. Although protease inhibitor exposure was not significantly associated with abnormal carotid ultrasound in our analysis, we found that longer duration of antiretroviral therapy was associated with an abnormal result.…”
Section: Discussioncontrasting
confidence: 83%
“…After adjusting for serum lipid levels, the relative risk remained significant at 1.10, suggesting that protease inhibitors contribute to cardiovascular disease through different mechanisms. Previous observational studies that investigated the relationship between protease inhibitor and carotid plaques produced conflicting results [19,23,[29][30][31]. Maggi demonstrated that protease inhibitor exposure was associated with carotid plaques [29,30] while other observational studies failed to show this association [19,23,31].…”
Section: Discussionmentioning
confidence: 99%
“…16 Others have found that patients with higher CD4 cell counts (> 200 cells/mm 3 ) had higher rates of vessel thickening, a surrogate marker for CVD, than patients with lower CD4 cell counts. 20 Female gender was one of the strongest predictors of MS in our study, despite a male predominance in the sample population. While a very high prevalence of MS among females from the USA has been reported recently, 21 this finding is rather unique in the literature, and may represent a distinctive feature of the Latin American region.…”
Section: Discussionmentioning
confidence: 50%
“…9 A number of previous studies has shown an association between use of protease inhibitors and early vascular structural and functional changes in HIV-infected children 23,24 and adults. 4,5,25 In particular, endothelial dysfunction, 5 increased carotid intima-media thickness, 25 and carotid atherosclerotic plaques 4 have been reported in HIV-infected adults. Several potential mechanisms may underlie the association between treatment with protease inhibitors and large-artery stiffness.…”
Section: Schillaci Et Al Hiv Infection and Aortic Stiffnessmentioning
confidence: 99%
“…This finding supports the hypothesis that immunodepression determined by HIV infection might in itself contribute to accelerate the atherosclerotic process. 4,24,25 Dyslipidemia, insulin resistance, inflammation, impaired fibrinolysis, and activation of vascular endothelium mediated by chronic HIV-induced low-grade inflammation 31,32 may also play a role in this regard.…”
Section: Schillaci Et Al Hiv Infection and Aortic Stiffnessmentioning
confidence: 99%